Prevalence of sarcopenia and its associated factors in patients attending geriatric clinics in Vietnam: a cross-sectional study. Issue 9 (17th September 2020) - Nguyen, Tam Ngoc; Nguyen, Tu Ngoc; Nguyen, Anh Trung; Nguyen, Thanh Xuan; Nguyen, Huong Thu Thi; Nguyen, Thu Thi Hoai; Pham, Thang; Vu, Huyen Thanh Thi
Abstract : Objectives: This study aims to investigate the prevalence of sarcopenia and its associated factors in patients attending geriatric clinics in Vietnam. Design and setting: A cross-sectional study was conducted in consecutive patients aged ≥60 visiting outpatient clinics of the National Geriatric Hospital in Hanoi, Vietnam, from January 2018 to October 2018. Handgrip strength was measured with a hand dynamometer. Whole-body dual-energy X-ray absorptiometry was applied to measure the appendicular skeletal muscle mass. Sarcopenia was defined by the criteria proposed by the Asian Working Group for Sarcopenia (AWGS 2019) and by the Foundation for the National Institutes of Health (FNIH) Sarcopenia Project. Results: There were 600 participants, mean age 70.0±8.0, 60.8% female. The prevalence of sarcopenia was 54.7% according to AWGS 2019 criteria and 40.5% according to FNIH. In multivariate logistic regression, age (adjusted OR 1.08, 95% CI 1.05 to 1.11), male (adjusted OR 2.03, 95% CI 1.29 to 3.21), underweight (adjusted OR 2.32, 95% CI 1.22 to 4.41), being malnourished (adjusted OR 3.77, 95% CI 1.19 to 11.91), chronic lung diseases (adjusted OR 3.48, 95% CI 2.10 to 5.77) and lower physical activity were significantly associated with sarcopenia defined by AWGS 2019 criteria. With FNIH definition, the significantly associated factors were age (adjusted OR 1.07, 95% CI 1.04 to 1.11), male (adjusted OR 6.78, 95% CI 4.12 to 11.17), low education (adjusted OR 2.15, 95% CI 1.27 to 3.63), being malnourished (adjusted OR 3.35, 95% CI 1.28 to 8.76), chronic lung diseases (adjusted OR 2.58, 95% CI 1.56 to 4.28) and lower physical activity level. Conclusion: The prevalence of sarcopenia in patients attending geriatric clinics was high. Further studies are needed to examine the impact of sarcopenia on adverse outcomes in this population.